Exosomes as biomimetic tools for stem cell differentiation: Applications in dental pulp tissue regeneration. (December 2016) - Huang, Chun-Chieh; Narayanan, Raghuvaran; Alapati, Satish; Ravindran, Sriram
Abstract: Achieving and maintaining safe and reliable lineage specific differentiation of stem cells is important for clinical translation of tissue engineering strategies. In an effort to circumvent the multitude of problems arising from the usage of growth factors and growth factor delivery systems, we have explored the use of exosomes as biomimetic tools to induce stem cell differentiation. Working on the hypothesis that cell-type specific exosomes can trigger lineage-specific differentiation of stem cells, we have evaluated the potential of exosomes derived from dental pulp cells cultured on under growth and odontogenic differentiation conditions to induce odontogenic differentiation of naïve human dental pulp stem cells (DPSCs) and human bone marrow derived stromal cells (HMSCs) in vitro and in vivo. Results indicate that the exosomes can bind to matrix proteins such as type I collagen and fibronectin enabling them to be tethered to biomaterials. The exosomes are endocytosed by both DPSCs and HMSCs in a dose-dependent and saturable manner via the caveolar endocytic mechanism and trigger the P38 mitogen activated protein kinase (MAPK) pathway. In addition, the exosomes also trigger the increased expression of genes required for odontogenic differentiation. When tested in vivo in a tooth root slice model with DPSCs, the exosomes triggered regeneration of dental pulp-like tissue. However, our results indicate that exosomes isolated under odontogenic conditions are better inducers of stem cell differentiation and tissue regeneration. Overall, our results highlight the potential exosomes as biomimetic tools to induce lineage specific differentiation of stem cells. Our results also show the importance of considering the source and state of exosome donor cells before a choice is made for therapeutic applications.